Pengelolaan Sumber Daya Energi Berbasis Lingkungan dalam Rangka Mewujudkan Negara Kesejahteraan - IGAK Rachmi Handayani; Edi As'adi; Sartika Bani Kharisma (Fakultas Hukum Universitas Islam Indonesia, 2017)
Today the energy resource management in realizing the prosperity concept as the aspiration of Indonesia people tends to threat the sustainability of living environment of Indonesian people that, in fact, also becomes the objective of state to protect all Indonesia people and all areas of Indonesia. Based on the explanation of this background, the problems in living environment-based energy resource management for Indonesia people arise. Those problems include first, the legal-politic in managing the energy resource today; second, inconsistency of legal politics in the energy resource management towards the sustainability of living environment and third, legal politics in managing the living environment-based energy resource in future. This is a normative research that concluded that first, normatively and sociologically, the management of the energy resource today tends to ignore any values of living environment-based local wisdoms. Second, capitalism and liberalism in energy resource management today tends to threat the sustainability of living environment of Indonesia people. Third, in future, there is a need for legal politics of the integral, comprehensive and continuous living environment based energy resource management.